PENGARUH KINERJA DOSEN TERHADAP MOTIVASI BELAJAR MAHASISWA - Jawasi Jawasi; Manalullaili Manalullaili; Hamidah Hamidah (Yonetim Jurnal, 2022)
The purpose of this study was to determine the effect of lecturer performance on student learning motivation so that learning can be optimized in accordance with campus academic guidelines. The method in this study was quantitative using simple linear regression analysis with a sample of 220 respondents. The primary data source used a questionnaire which was distributed to respondents according to the sample in this study. The results of the study obtained a significance value of 0.456 so that there was no effect of lecturer performance on student learning motivation. And the R Square value in the determinant coefficient table is 0.003, which means that the influence of the lecturer's performance variable on learning motivation is 0.30%, it can be assumed that there are many other factors that influence student learning motivation that are not examined in this study such as family relationships, relationships with friends peers, infrastructure and so forth.